2021
DOI: 10.3389/fphar.2021.710722
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Gastrodin in Type 2 Diabetes Mellitus and Its Mechanism

Abstract: As a severe metabolic disease, type 2 diabetes mellitus (T2DM) has become a serious threat to human health in recent years. Gastrodin, as a primary chemical constituent in Gastrodia elata Blume, has antidiabetic effects. However, the possible mechanisms are unclear. The aim of the present study was to investigate the effects and possible mechanisms of gastrodin on the treatment of T2DM. In vivo, after treatment with gastrodin for 6 weeks, fasting blood glucose levels, blood lipid metabolism, and insulin sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Recently, USP has been reported to be involved in glucose metabolism (Forand et al 2016;Hashimoto et al 2022), lipid metabolism (Ni et al 2020), type 2 diabetes mellitus (Bai et al 2021), and nonalcoholic fatty liver disease (An et al 2017;Zhao et al 2018). Proteasome transiently interacts with proteasome-interacting proteins (PIPs), which are not proteasome subunits but are involved in the function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, USP has been reported to be involved in glucose metabolism (Forand et al 2016;Hashimoto et al 2022), lipid metabolism (Ni et al 2020), type 2 diabetes mellitus (Bai et al 2021), and nonalcoholic fatty liver disease (An et al 2017;Zhao et al 2018). Proteasome transiently interacts with proteasome-interacting proteins (PIPs), which are not proteasome subunits but are involved in the function.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical trials have found the bene cial outcome of Gastrodin on patients with vascular dementia [8,30]. Though many studies have found that Gastrodin treated diabetes through PI3K/AKT pathway [31,32], our study was the rst to report that the PAK2 is important for the effect of Gastrodin. Our result also found that 60 mg/kg of Gastrodin intervention had a better outcome than 120 mg/kg.…”
Section: Discussionmentioning
confidence: 65%
“…A report suggested that USP4 might also mediate the beneficial effects of traditional medicine in the context of insulin signaling. Gastrodin, a chemical derived from Gastrodia elata Blume (Orchidaceae), significantly decreased dexamethasone-induced ubiquitination of insulin receptors in HepG2 cells, and concomitant increases of USP4 mRNA and protein were also observed [ 113 ]. Mechanistically, gastrodin suppressed the association of GATA binding protein 1 (GATA1) with the Usp4 promoter, suggesting that gastrodin likely increases USP4 transcription in a GATA1-dependent manner [ 113 ].…”
Section: Diabetes Mellitus and Insulin Resistancementioning
confidence: 99%